Experimental investigation on the VIV of a slender body under the combination of uniform flow and top-end surge. (15th November 2020) - Zhang, Cheng; Kang, Zhuang; Stoesser, Thorsten; Xie, Zhihua; Massie, Lucy
Abstract: In order to investigate the effect caused by floating bodies on vortex-induced vibration (VIV) of risers, a composite pipe with the aspect ratio of 250 is tested under coupled uniform and shear oscillatory flow, with Reynolds number ranging from 2000 to 24000. The characteristics of VIV amplitude and frequency of the model under uniform flow are compared and analyzed comprehensively, alongside experimental results from literature, validating the reasonability of the test devices and methods. The key characteristics of VIV under coupled top-end surge and uniform flow are then discussed. Some phenomena involving time-varying frequency, mode transition, amplitude modulation and so on are induced by the oscillation of flow, which also promotes the generation of high-order and low-order harmonic components in cross-flow and in-line frequencies. When combined with uniform flow, the identification of time-varying frequency and amplitude modulation is significantly enhanced by uniform flow with lower velocities while the top-end surge mainly affects the vibration instability in higher-velocity uniform flow. The oscillation amplitude and frequency of the top-end surge mainly change the values of cross-flow vibration amplitude, but affect the in-line amplitude both for trend and values, inducing the increase of values in the range of medium and low reduced velocities and the changing of the distribution of reduced velocity corresponding to the local maximums in the higher range. The combination of the top-end surge related to the movement of floating body and the background flow is responsible for the high-order harmonics of VIV frequency and the enhancement of VIV amplitude under certain reduced velocities, which may induce additional fatigue damage of riser. It is suggested that the movement of floating body should be taken into account in the evaluation of VIV of risers. Highlights: The VIV of a flexible model under top-end surge and uniform flow is investigated experimentally. The intermittent VIV is induced by top-end surge, which could be enhanced by uniform flow with low and medium velocities. For high velocity cases, the VIV is dominated by uniform flow while top-end surge plays a disturbing role. The effects of the surge amplitude and frequency on VIV are related to uniform flow velocity and vibration direction.